Impact of the COVID-19 Pandemic Lockdown on Routine Childhood Immunization: A Saudi Nationwide Cross-Sectional Study - Baghdadi, Leena R.; Younis, Afnan; Al Suwaidan, Hessah I.; Hassounah, Marwah M.; Al Khalifah, Reem (Frontiers in Pediatrics, 2021)
Background: Routine childhood immunization is the most cost-effective method to prevent infection and decrease childhood morbidity and mortality. The COVID-19 pandemic has affected access to health care in Saudi Arabia, including mandatory vaccinations for young children. We aimed to assess the prevalence of intentionally delayed vaccinations in children aged ≤2 years during the COVID-19 pandemic curfew in Saudi Arabia, its relation to the caregivers’ fear of infection, and identifying factors affecting the caregivers’ decision. Methods: We conducted a cross-sectional study using a self-administered survey that targeted primary caregivers of children aged ≤2 years residing in Saudi Arabia during the COVID-19 pandemic curfew (March 4–July 6, 2020). Results: We received responses from 577 caregivers, of whom 90.8% were mothers. The prevalence of intentional vaccination delay was 37%. Upon adjusting the potential confounders, the odds of delaying scheduled childhood vaccination because of COVID-19 pandemic fears were greater among caregivers with higher levels of fear (OR 1.10, 95% CI 1.02-1.11). Common reasons for delaying vaccinations were COVID-19 infection and prevention of exposure to COVID-19 cases. Conclusion: Intentional vaccination delay leaves young children vulnerable to preventable infectious diseases. Identifying these children and offering catch-up vaccinations reduces this risk. Campaigns to increase awareness about the dangers of delaying vaccine-preventable diseases must be promoted to caregivers in addition to the promotion of home vaccination services. In preparation for future pandemics, we recommend countries consider interventions to control the level of fear and anxiety provoked by the pandemics and media, and interventions for improved access to vaccinations.